PERLINDUNGAN HUKUM TERHADAP PASIEN SEBAGAI KONSUMEN KESEHATAN DITINJAU DARI HUKUM PERDATA, PIDANA DAN ADMINISTRASI - Fransiska Novita Eleanora (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
Patient as consumer commodity/service at least gets enjoyment and satisfaction especially in health service given by medical doctor, nurse and the side of hospital. But in fact, exactly many happened loss experienced by patient and results the patient is handicap, even pass away action effect from the side of doctor/nurse/hospital pain in curing. Protection of law to patient. consumer can be done in civil, criminal and Administration. Responsibility in civil through default or deed fights against law, criminally existence of assertive sanction and explains in sections in Criminal Law and in Administration existence of repeal of permit from practice and permit from work. Show that is bibliography study, the result is how protection of law got by patient as consumer and applying of sanction to medical doctor conducting action malpractice in civil, criminal and administration.